Limitations in the assessment of radon dose: the role of activity measurements in the human body - Kalef-Ezra, J.; Valakis, S. (HNPS Advances in Nuclear Physics, 2019)
Radon-222 is classified in the Group I of the human carcinogens. The in situ decay of inhaled 222Rn and its short-lived decay products (T1/2 <30 min) is the main source of radiation burden to the general population of natural origin. The corresponding effective dose is routinely calculated as the product of the 222Rn concentration in air, a predetermined dosimetric constant and a factor that depends on the space type (e.g. residential or public building, cave, mine, etc). However, in practice, there are large spatial and temporal variations in the activity ratio of each progeny to 222Rn in air, the characteristics of the progeny carrying particles and the metabolism of each progeny depending on air quality, as well as differences in the anatomic and physiological characteristics between individuals, that vary substantially even with time. Therefore, the currently employed dosimetric approach may introduce large uncertainties. In the hypothetical case of acute deposition and full retention in the human body of equal activities of all 222Rn progeny, about 93% of the effective dose is due to the decaying 214Po. The 214Po activity can be assessed by measurement of its γ-emitting precursor, 214Bi, which is in full equilibrium with 214Po in the human body. The 214Bi activity can be measured using a high-sensitivity whole-body counter with high counting uniformity, such as the one in use at the Ioannina University Medical Physics Department. Its detection efficiency and its dependence on body shape and size were assessed by Monte Carlo simulations. Measurements carried out in healthy adult volunteers residing at a short distance from the counter, indicated a mean total body 214Bi activity (TBBi) of 100 Bq during the cold season of the year and lower during the hot one. Higher mean TBBi levels were found in male than in female adults. Therefore, TBBi measurements may allow for accurate radon-related risk assessment on individual base.